HUBUNGAN BENTUK AKTIVITAS YANG MENDASARI TIMBULNYA HUMOR DENGAN PELANGGARAN MAKSIM PADA ACARA RAGAM AKBINGO! - Anindya Kartika; Kusumawati, Adis (Japanology: The Journal of Japanese Studies, 2019)
A speech act that violates the maxim can cause humor. Humor is an important role in entertainment programs. One of the Japanese entertainment programs in which there are many acts of speech violating the maxim of linguistic principles is the AKBINGO! This variety program has been aired since 2008 until now. Not only violations of the maxims of the utterances uttered by the performers in AKBINGO !, the forms of activities carried out can also invite audience laughter. Speech act theory, the principle of cooperation and politeness theory as well as the theory of activity forms that underlie the emergence of a humorous activity are used to analyze speech and activities that can invite laughter in this television program. The research method used is the literature study method and the matching method. Based on the results of the study, it was found 153 maxim violations that invited humor and there were 87 forms of activity that cause humorous activities. There is relation between the types of activities that cause humorous activity with violations of maxims that are carried out because there are similarities in the way they form humor.